Optimasi Load Balancing dan DNS pada CDN untuk Mempercepat Distribusi Konten menggunakan BIND dan HAProxy berbasis Linux - Darujati, Cahyo; Al Azam, Moh Noor; Prihadi, Novi Mustar (Institut Teknologi Adhi Tama Surabaya, 2024)
This research explores how to make content delivery faster using a Content Delivery Network (CDN) on Linux, focusing on optimizing DNS and load balancing with tools like BIND and HAProxy. It’s all about ensuring users get content quickly, no matter where they are. Set up three edge servers running HAProxy for load balancing and one BIND server for DNS, using a feature called geodns to direct users to the nearest server. We simulated users from different locations to mimic real-world use. Data was collected using tools like tcpdump for network traffic, Apache Bench for HTTP performance, and system monitoring tools to track CPU and memory usage. We measured latency (time to first byte), throughput (data speed), CPU usage, and error rates. Baseline: No optimizations, with latency at 244.2 ms, throughput at 100 MB/s, CPU usage at 70% with 15% variation, and 5% error rate. Geodns Only: Latency dropped to 111.2 ms, keeping throughput at 100 MB/s. Load Balancing Only: Throughput rose to 120 MB/s, CPU usage balanced to 60% with 5% variation, and error rate fell to 3%. Combined: Best results with latency at 107.2 ms, throughput at 120 MB/s, and error rate at 2%. An interesting detail is how geodns not only lowers latency but also helps balance server loads, which is especially useful in places like Indonesia with uneven user distribution. Combining both optimizations significantly boosts CDN performance, making it a great approach for content providers. It’s clear this can improve user experience, especially in areas with varied network setups.